Efficacy and safety of zhibitai in the treatment of hyperlipidemia: A systematic review and meta-analysis - Wang, Chunyang; Pang, Wentai; Du, Xuechen; Zhai, Jiani; Zhong, Mengyuan; Zhuang, Ming; An, Jiali; Cao, Lujia; Zhang, Li; Zheng, Wenke; Zhang, Junhua (Frontiers in Pharmacology, 2022)
Objective: To evaluate the efficacy and safety of Zhibitai (ZBT) in the treatment of patients with hyperlipidemia (HLP). Methods: A search of 8 electronic databases was conducted to find randomized controlled trials (RCTs), to evaluate the efficacy and safety of ZBT for the treatment of HLP. The risk of bias in randomized controlled trials was assessed by using the Cochrane Collaboration Risk of Bias tool for randomized controlled trials 2.0 (RoB 2.0). The primary outcomes were the levels of triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C). The total effective rate served as the secondary outcome. The incidence of adverse events was considered the safety outcome. Review Manager 5.4 was used to conduct meta-analyses. Data were pooled by random-effects or fixed-effects model to obtain the mean difference (MD), risk ratio (RR), odds ratio (OR), and 95% confidence interval (CI). Results: There were 28 eligible RCTs with a total of 2,952 participants. Overall, we verified that ZBT plus conventional therapy (CT) was superior to CT for the treatment of HLP [TC: MD = −0.50, 95% CI (−0.80, −0.19); TG: MD = −0.38, 95% CI (−0.49, −0.27); LDL-C: MD = −0.50, 95% CI (−0.69, −0.31); HDL-C: MD = 0.17, 95% CI (0.11, 0.24); total effective rate: OR = 4.26, 95% CI (2.28, 7.95)]. There were no significant differences in the primary outcomes between ZBT alone vs. CT (p > 0.05). For safety, the ZBT group (with CT or alone) outperformed the CT group [ZBT alone: RR = 0.51, 95% CI (0.32, 0.81); ZBT plus CT: RR = 0.51, 95% CI (0.30, 0.89)]. For each outcome, the subgroups and the sensitivity analysis matched the overall results. Conclusion: ZBT may be safe and beneficial to HLP patients, especially for serum lipid management. ZBT can be used along with CT for the treatment of HLP. However, it is necessary to conduct more rigorous RCTs to confirm these findings. Systematic Review Registration: [https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42022316251].